Modeling of High‐Pressure Ethene Homo‐ and Copolymerization. Issue 5 (11th February 2019) - Peikert, Paul; Pflug, Kristina M.; Busch, Markus
Abstract: While reaction engineering of low‐molecular weight compounds mainly focuses on equilibria and selectivities, polymer properties are tremendously influenced by molecular weight distribution as well as branching structure. In order to determine the branching structure of low‐density polyethylene (LDPE) copolymers in dependence on chosen process conditions, a Monte‐Carlo approach was developed. By modeling the topology as well as the comonomer distribution in the polymer chains a deeper insight in the process‐microstructure‐properties relationship is gained. Abstract : A highly efficient stochastic copolymerization approach has been developed, which stores the branching structure as well as the comonomer position for an ensemble of up to 50 million macromolecules. The stored data is then evaluated in order to investigate the influence of process conditions on microstructure as well as product properties.